A 0.8 V T Network-Based 2.6 GHz Downconverter RFIC - Wu, Jian-Ming; Liou, Ching-Kuo; Chuang, Ching-Jui; Kuo, Yujin (Společnost pro radioelektronické inženýrství, 2012)
A 2.6 GHz downconverter RFIC is designed and implemented using a 0.18 μm CMOS standard process. An important goal of the design is to achieve the high linearity that is required in WiMAX systems with a low supply voltage. A passive T phase-shift network is used as an RF input stage in a Gilbert cell to reduce supply voltage. A single supply voltage of 0.8 V is used with a power consumption of 5.87 mW. The T network-based downconverter achieves a conversion gain (CG) of 5 dB, a single-sideband noise figure (NF) of 16.16 dB, an RF-to-IF isolation of greater than 20 dB, and an input-referred third-order intercept point (IIP3) of 1 dBm when the LO power of -13 dBm is applied.
Keywords: Downconverter; mixer; low voltage.